Limnological Condition of the Pekak Lake,based on physical-chemical parameters Buluh Nipis Village, Kampar District, Riau Province - Br. Allagan, Desima Kristina; Siagian, Madju; H. Simarmata, Asmika (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractPekak Lake is one of oxbow lakes located in the Buluh Nipis Village. A research aims to understand the limnological condition of the Pekak Lake based on physical – chemical parameters has been conducted in March-April 2018. There were three sampling stations namely Station 1 (inlet), Station 2 (in the middle of the lake), and Station 3 (outlet). In each station there were two sampling points, in the surface (0 cm) and 1 Secchi depth (75 cm). Samplings were done once/week for 3 weeks period. Water quality parameters measured were temperature, transparency, depth, pH, DO, CO2 free, nitrate and phosphate concentration. Result shown that the temperature 28.6-300C, transparency 68.5– 76.83 cm, depth 1.45 – 2.70 m, pH 5 , DO 5.13-6.4 mg/L, CO2 free 8.23-15.48 mg/L, nitrate 0.05 – 0.19 mg/L and phosphate 0.06 – 0.11 mg/L.  Based on the nitrate and phosphate concentrations, Pekak Lake can be categorized oligotrophic- mesotrophic. Keyword : Oxbow Lake, Water Quality, Oligotrophic, Mesotrophic